Lived experience of nutrition impact symptoms among patients undergoing chemotherapy in Ethiopia: An interpretative phenomenological analysis - Awole Seid; Zelalem Debebe; Abebe Ayelign; Bilal Shikur Endris; Mathewos Assefa; Ahmedin Jemal (PLoS ONE, 2025)
Background Nutrition impact symptoms such as nausea, vomiting, and taste alterations are common side effects of chemotherapy and can lead to malnutrition. There is a paucity of data regarding the nutritional challenges faced by cancer patients, particularly in resource-limited settings. This study aimed to explore the lived experiences of nutrition impact symptoms among patients undergoing chemotherapy at a major cancer center in Ethiopia. Methods An interpretative phenomenological analysis was conducted from November 11–29, 2024, involving 26 cancer patients treated at the Oncology Center of Tikur Anbesa Specialized Hospital, Addis Ababa, Ethiopia. Both data and thematic saturation were employed to determine the sample size. Participants were selected using heterogeneous sampling, and data were collected through in-depth interviews. The interviews were audio-recorded and transcribed verbatim in Amharic, followed by a contextual translation into English. The data were analyzed using an inductive thematic analysis approach with the aid of MAXQDA24 software. Results Three themes were identified: symptom burden and coping, individualized food choices, and unmet nutritional support needs. Symptoms were particularly severe during the early stages of treatment, disrupting typical dietary patterns and leading to physical limitations, negative emotional responses, and decreased productivity. The finding also revealed financial barriers to accessing nutritious foods, nutritional misinformation, and unsatisfactory experiences with hospital food. Conclusion Symptoms vary in onset, severity, and pattern among individuals, significantly impacting their quality of life. Nutritional support is a pressing need for cancer patients. The findings underscore the critical need for dietitian-led, patient-centered nutritional interventions, along with socioeconomic support for patients undergoing chemotherapy in Ethiopia.